EDUKASI PENCEGAHAN TERHADAP KEJADIAN KELUHAN MUSCULOSKELETAL DISORDER PADA PEKERJA CAKE AND BAKERY DI KABUPATEN PONOROGO - Bintang Saputri, Triasti; Sri Sunaringsih Ika Wardojo (Rena Cipta Mandiri, 2025)
Musculoskeletal disorders (MSDs) are one of the most common hazards experienced by workers where injuries occur to muscles, tendons, ligaments, and joints due to continuous static work activities over a long period of time. There are several factors that cause musculoskeletal disorders, such as age, gender, work attitude, and work duration. The purpose of this activity is to increase the level of worker knowledge of MSDs and identify workers' MSD complaints. This activity method uses primary data through observation and Nordic Body Map measurements and a pre-post questionnaire to determine the level of worker knowledge about MSDs. The results found that the majority of workers experienced complaints in the back area (12 people (46%) and the lower neck area (8 people (30%), as well as an increase in knowledge about MSDs.